Course Information System Using Codeigniter Framework - Anisa Novianti; Rr. Isni Anisah Puspowati; Titi Widaretna; Nanang Suciyono; Susanto Susanto (Informatics Management, Engineering and Information System Journal, 2025)
This study examines the inefficiencies encountered by a training institution in Bandung Regency that utilizes a manual handwritten ledger for managing diverse data, including student information, teacher records, class details, student learning progress, and grades.  The current technique results in considerable delays in information retrieval, as perusing physical data is often time-intensive.  Moreover, producing reports for institutional control becomes burdensome, eliciting apprehensions of data accuracy, potential harm, or loss of vital information.  To address these challenges, we created a course information system utilizing the CodeIgniter framework.  The study utilized a descriptive methodology, and the system development applied Object-Oriented Analysis and Design (OOAD) concepts.  We employed Unified Modelling Language (UML) methodologies during the software design process.  The newly created course information system aims to streamline user data management and enhance the efficiency of recording operations for all participants, including administrators and educators.  The digitization of information management decreases retrieval times and enhances data accuracy and security, consequently promoting improved decision-making and reporting within the institution.